Is there a correlation between coaches` leadership styles and injuries in elite football teams? A study of 36 elite teams in 17 countries - Ekstrand, J.; Lundqvist, D.; Lagerbäck, L.; Vouillamoz, M.; Papadimitiou, N.; Karlsson, J. (British Journal of Sports Medicine, 2017)
Background: Do coaches` leadership styles affect injury rates and the availability of players in professional football? Certain types of leadership behaviour may cause stress and have a negative impact on players` health and well-being. Aim: To investigate the transformational leadership styles of head coaches in elite men`s football and to evaluate the correlation between leadership styles, injury rates and players` availability. Methods: Medical staff from 36 elite football clubs in 17 European countries produced 77 reports at four postseason meetings with a view to assessing their perception of the type of leadership exhibited by the head coaches of their respective teams using the Global Transformational Leadership scale. At the same time, they also recorded details of individual players` exposure to football and time-loss injuries. Results: There was a negative correlation between the overall level of transformational leadership and the incidence of severe injuries (rho=-0.248; n=77; p=0.030); high levels of transformational leadership were associated with smaller numbers of severe injuries. Global Transformational Leadership only explained 6% of variation in the incidence of severe injuries (r2=0.062). The incidence of severe injuries was lower at clubs where coaches communicated a clear and positive vision, supported staff members and gave players encouragement and recognition. Players` attendance rates at training were higher in teams where coaches gave encouragement and recognition to staff members, encouraged innovative thinking, fostered trust and cooperation and acted as role models. Conclusions: There is an association between injury rates and players` availability and the leadership style of the head coach. Abstract from author